Emission of inorganic particulate matter during the combustion of biomass, biochar and Collie coal - Gao, Xiangpeng (Curtin University, 2011)
Coal is an important part of Australia's energy mix and is expected to continue to play an essential role in supplying cheap and secure energy for powering the Australian economy in the foreseeable future. However, coal-based stationary electricity generation is a key contributor to greenhouse gas (e.g. CO2) emission, which is widely believed to be responsible for global warming and problems related to climate change. Therefore, renewable energy sources such as biomass are becoming increasingly important. In Australia, mallee biomass as a byproduct of managing dryland salinity in agricultural land is a truly sustainable second generation feedstock. Its production is economic, of large scale, high energy efficiency and low carbon footprint. Therefore, mallee biomass and its derived fuels such as biochars can potentially play a key role in the future energy mix of Australia due to significant benefits in Australia's energy security and sustainable development.Direct combustion of solid fuels (e.g. coal, mallee biomass and its derived biochars etc) is considered to be a matured technology. Coal combustion or coal/biomass co-firing is widely deployed for power generation. However, ash-related issues during solid fuels combustion are notorious and must be considered, particularly the formation/emission of fine inorganic particulate matter (PM). Fine PM is responsible for initiating ash deposition and corrosion on heat exchanger surfaces. PM emission also causes significant adverse impact to human health and environment. Despite the research progress made in this area in the past two decades, there are still significant research gaps in developing credible PM sampling method and understanding on formation/emission of inorganic PM during the combustion of biomass and/or coal.The present study aims to carry out a systematic study to obtain a thorough understanding on the emission of inorganic PM during the combustion of biomass, biochar and coal. The specific objectives of this research are to: (1) investigate the effect of sampling temperature on the properties of PM with a size less than 10μm (PM10) produced from pulverized mallee biomass combustion, then develop a proper sampling method for PM produced from the combustion of solid fuels (e.g. biomass and coal); (2) examine the emission behavior and characteristics of PM10 produced from pulverized biochar combustion, in order to provide useful data for the design of biochar-based combustion systems; (3) assess the importance and provide direct experimental evidences on the contribution of volatiles combustion to the emission of PM with a size less than 1.0μm (PM1), and to give insights into fundamental understanding on fine PM formation/emission during biomass combustion; and (4) reveal the significant roles of inherent fine included mineral particles in the emission of PM10 during pulverized coal combustion, and propose essential guideline for coal selection on its potential in fine inorganic PM emission during combustion. These objectives have been successfully achieved in this PhD study.Firstly, sampling temperature is found to influence significantly on the properties of PM10 collected from the combustion of pulverized mallee biomass. Although the yield of PM1 as well as the mass of its dominant elements (e.g. Na, K and Cl) in PM1 remain constant, the mass-based particle size distribution (PSD) of PM1 and elemental-mass-based PSDs of Na, K and Cl in PM1 shift to a larger size at a lower sampling temperature, apparently due to particulate coagulation. However, increasing sampling temperature reduces PM loss due to gravitational settling deposition, leading to an increase in the yields of the PM in a size range of 1.0 – 10 μm (PM1-10) and its dominant elements such as Mg and Ca. Both the yields of PM1-10 and the mass of Mg and Ca in PM1-10 reach constant values at sampling temperatures close to the flue gas temperature (115oC). The sampling temperatures at which drastic shifts in PSD and elemental-mass-based PSDs of PM10 take place correlate well with the SO3 dew points of the flue gas. Therefore, the sampling temperature of PM should be above the flue gas acid dew point to prevent the condensation of acid gas and furthermore be kept close to or same as the flue gas temperature in order to suppress particulate coagulation and gravitational settling deposition. Based on this important finding, a proper PM sampling method is therefore developed.Secondly, the PSD of PM10 from raw biomass combustion has a bimodal size distribution while the PSDs of PM10 from the combustion biochars generally show a unimodal distribution. Most of alkali and alkaline earth metallic species (AAEM species, mainly Na, K, Mg and Ca) are retained in the biochar during pyrolysis. However, the combustion of biochars leads to a significant reduction in the emission of PM1 (and the mass of Na, K and Cl in PM1) that dominantly consists of particles smaller than 0.1 μm (PM0.1) in comparison to biomass combustion, apparently because of the removal of volatiles and Cl from the raw biomass during pyrolysis for biochars preparation. The results imply that the combustion of volatiles (including the released inorganic species), which is particularly important during biomass combustion, is mainly responsible for PM1 emission. Meanwhile, a considerable increase in the emission of PM1-10 (and the mass of Mg and Ca in PM1-10) is also evident during biochar combustion, most likely as a result of more porous structure and increased ash loading of biochars.Thirdly, a novel two-stage pyrolysis/combustion system is therefore designed to obtain the direct experimental evidence on the contribution of volatiles combustion to PM emission. The combustion of Na-, K- and Cl-containing volatiles, which are produced in situ from the fast pyrolysis of mallee biomass, contributes substantially to PM1 emission. The PM1 yield from volatiles combustion is 77.4 – 89.3% of total PM1 collected from the combustion of both volatiles and char. Oppositely, 97.5 – 99.7% of the yields of total PM1-10 are from char combustion. An increase in pyrolysis temperature leads to an increase in the PM0.1 yields and the mass of Na, K and Cl in PM0.1 from volatiles combustion, as results of enhanced volatilization of Na, K and Cl during pyrolysis. The mass-based PSDs of PM10 and elemental-mass-based PSDs of Na, K, and Cl (which are dominantly contained in PM1) from volatiles combustion generally show a unimodal distribution with a fine mode range from ~0.022 to ~0.043 μm. The mass-based PSDs of PM10 and elemental-mass-based PSDs of Mg and Ca (which are dominantly contained in PM1-10) from char combustion also generally show a unimodal distribution but with a coarse mode of ~6.8 μm. The results clearly demonstrate that the combustion of volatiles (therefore Na, K and Cl included) produced in situ from the fast pyrolysis of biomass is a key mechanism responsible for PM1 emission.Finally, a density-separated coal sample, with a specific gravity of 1.4 – 1.6, is prepared from Collie coal. As expected, the data of computer-controlled scanning electron microscopy (CCSEM) analysis on the coal show that mineral matter in the coal is of included nature, of which ~90% are fine mineral particles <10 μm. The PM10 collected from the combustion of coal and char samples dominantly contains PM1-10, while the yields of PM1 are limited. PM1-10 contains mainly refractory species, including Si, Al, Fe, Mg and Ca. The data also show that PM1 from char combustion consists of two major fractions with different chemical composition, i.e., PM0.1 and PM in a size range of 0.1 – 1 μm (PM0.1-1). PM0.1 dominantly contains volatile elements (such as Na, K, P and S) and also some refractory elements (e.g. Fe and Si) but PM0.1-1 is mainly composed of refractory elements (Al, Fe, and Si). The vast existence of aluminosilicates in PM0.1-1 indicates the significant roles of fine included kaolinite and/or Al-silicates particles in the emission of PM1 from char combustion. Furthermore, the significant roles of inherent fine included mineral particles in PM1-10 emission during the combustion of coal and char are clearly evidenced via the identification of the presence of abundant individual but partially-molten quartz ash particles in PM1-10.